1998
DOI: 10.1016/s0169-5150(98)00027-9
|View full text |Cite
|
Sign up to set email alerts
|

Market access by smallholder farmers in Malawi: implications for technology adoption, agricultural productivity and crop income

Abstract: Journal articleISI; IFPRI3EPTDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(49 citation statements)
references
References 6 publications
2
46
1
Order By: Relevance
“…Small-scale cotton growers in Benin and producers of cashew nuts and tobacco in Tanzania have benefited from higher producer prices thanks to declining marketing margins and the depreciation of the real exchange rate. Similarly, following the liberalization of burley tobacco production and marketing in Malawi, increased tobacco production increased the cash income of smallholder farmers in that country (Box 5) 30 .…”
Section: Higher Export Crop Prices Have Benefited Export Crop Farmersmentioning
confidence: 99%
“…Small-scale cotton growers in Benin and producers of cashew nuts and tobacco in Tanzania have benefited from higher producer prices thanks to declining marketing margins and the depreciation of the real exchange rate. Similarly, following the liberalization of burley tobacco production and marketing in Malawi, increased tobacco production increased the cash income of smallholder farmers in that country (Box 5) 30 .…”
Section: Higher Export Crop Prices Have Benefited Export Crop Farmersmentioning
confidence: 99%
“…However, there are a number of studies pointing out that smallholders successfully adopt hybrid seeds (Smale, 1995;Heisey et al, 1998;Morris, 1998;Zeller et al, 1998). Although larger farmers tend to be early adopters of new seed technologies, small-scale farmers often significantly benefit from spillover effects.…”
Section: Introductionmentioning
confidence: 99%
“…Access to production credit greatly increases household willingness to invest in higher value crops and livestock. Credit is significant for farmers to buy necessary inputs such as fertilizer, seed, crop varieties, pesticides, animal feed and so on to improve farming productivity (Zeller et al, 1998). One study by Hazarika and Alwang (2003) found that credit helps farmers shift their labor-intensive technologies to capital-intensive technology via investments in machinery and new varieties.…”
Section: Introductionmentioning
confidence: 99%